Palangka Raya City Residents' Perceptions of the New Icon of the Bundaran Besar - Satria, Edi Burga; Harjum, Frederikus Vieri; Adiwijaya, Saputra; Batubara, Muhammad Zusanri; Saragih, Osi Karina; Manao, Willy (West Science Social and Humanities Studies, 2024)
The Grand Roundabout stands as a pivotal landmark in Palangkaraya, recently undergoing significant renovation and augmentation with new elements. This research employs a survey method, distributing questionnaires across various segments of society to acquire a comprehensive understanding of their perspectives. Findings indicate that the majority of Palangkaraya residents welcome these changes, considering their efforts to beautify the city and enhance tourism appeal. Overall, the new icon of the Grand Roundabout is deemed successful in representing Palangkaraya's modern and dynamic identity, although some aspects still require improvement. The renovation includes the addition of artistic and structural designed elements to reinforce the city's visual identity and attract more tourists. To grasp societal views, the survey method was utilized, reaching out to local residents, merchants, and tourists visiting the city. Research results show that most respondents positively embraced the changes at the Grand Roundabout, perceiving this new icon as a step forward in enhancing the city's aesthetics and tourism allure. Local communities express pride in the Roundabout's new appearance, considered more modern and reflective of Palangkaraya's progress. Many believe that the renovation brings a fresh ambiance and enhances the city's overall aesthetics. However, the survey also reveals some critiques and concerns. There are concerns regarding the renovation's impact on traffic around the Grand Roundabout, especially during peak hours, which could potentially lead to congestion. This research provides valuable insights for policymakers in designing and implementing similar projects in the future.